Atividade formicida de Pogostemon cablin e sua nanoformulação sobre formigas cortadeiras - Rocha, Anderson Góes (2015)
Leaf-cutting ants in the genus Atta are common insects in the Neotropics and important pests in agricultural and forestry environments. Ant control of this genus has been made with the use of synthetic organic insecticides, by often inefficiently. In this way, aiming generate new technology for the management of these pests, this work aimed to evaluate the essential oil activity from Pogostemon cablin against species of leaf-cutting ants Atta opaciceps, A. sexdens and A. sexdens rubropilosa and develop nanoformulation basis of this essential oil. The essential oil P. cablin was obtained by hydrodistillation of dry leaves and the identification/quantification of the compounds by was performed by GC/MS/FID. The nanoformulation (18%) was performed by magnetic shaking using essential oil from P. cablin, polyoxyethylene sorbitan, ethanol and water. Acute toxicity bioassays were conducted by fumigation, lethal time and behavioral. Behavioral studies involved pathway behavior bioassays in fully treated arenas and treated by half. Small variations were observed in the chemical composition of nanoformulation in relation to the essential oil from P. cablin. The essential oil from P. cablin and its nanoformulation demonstrated efficient insecticidal activity against the species A. opaciceps, A. sexdens and A. sexdens rubropilosa. The concentrations necessary to cause 50% mortality of workers by fumigation ranged from 1,06 a 2,10 μL L-1. The survival of workers of A. opaciceps, A. sexdens and A. sexdens rubropilosa exposed to essential oil from P. cablin and its nanoformulation was significantly reduced over time. The essential oil from P. cablin and its nanoformulation reduced the distance and the speed of workers of A. opaciceps and A. sexdens rubropilosa in fully treated arenas. The treatments didn’t affect the pathway behavior of workers of A. sexdens in these bioassays. While bioassays of arenas treated by half, when the insect had free choice, three species of ants walked less in the treated area and with greater speed. For A. sexdens rubropilosa this effect was more pronounced for the essential oil from P. cablin compared to nanoformulation of this oil. The species A. sexdens and A. sexdens rubropilosa remained most of the time on untreated side by essential oil from P. cablin or its nanoformulation. While A. opaciceps remained less time on the treated side with essential oil from P. cablin. This work demonstrates the strong formicidal activity of essential oil from P. cablin and the great potential of nanoformulation developed to generate new products.